Botanical Pesticide Applications for Sustainable Pest Management in Shallot-Based Cropping Systems - Disra Mislany; Abdul Azis Ambar; Muh. Ikbal Putera; Asysyura Asysyura (Edupedia Publisher, 2025)
Reducing dependency on synthetic pesticides is a central challenge in advancing sustainable horticultural production systems. This study evaluated the effectiveness of Lantana camara leaf extract as a botanical pesticide for managing Spodoptera exigua in shallot-based cropping systems under field conditions. A randomized complete block design was applied with four extract concentrations, and observations included pest infestation intensity, leaf damage progression, plant vigor, yield performance, and phytotoxicity. The results showed a clear dose-dependent reduction in infestation intensity, with the highest concentration achieving the greatest suppression, while the moderate concentration provided the optimal balance between pest control and crop performance. Treated plots exhibited delayed larval development, improved plant vigor, and higher yield compared to the untreated control. Mild phytotoxic effects were observed only at the highest concentration, indicating the importance of dosage optimization. These findings demonstrate that plant-derived extracts can effectively reduce pest pressure while maintaining crop productivity. The study highlights the potential of botanical pesticide applications as a component of sustainable pest management strategies within shallot-based cropping systems, supporting reduced chemical reliance and enhanced agroecosystem resilience.